THE EFFECT OF ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE LOYALTY AT PT TASPEN (PERSERO) KCU MEDAN - Muliani Syapitri; Annio Indah Lestari Nasution; Nurbaiti (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study aims to examine the effect of organizational culture and organizational commitment on employee loyalty at PT TASPEN (Persero) KCU Medan. Research Methodology: This research employed a quantitative approach using an explanatory associative research design. The study population consisted of 27 employees, and the entire population was selected as respondents through a saturated sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression analysis with the assistance of IBM SPSS Statistics version 29. Results: The findings indicate that organizational culture and organizational commitment partially have a positive and significant effect on employee loyalty. Furthermore, the simultaneous test results show an F-value of 36.990 with a significance level of 0.001, demonstrating that both independent variables collectively contribute a positive and significant effect on employee loyalty. Conclusions: These findings suggest that stronger implementation of organizational culture and higher levels of organizational commitment among employees are associated with increased employee loyalty toward the company. Limitations: This study is limited by the relatively small number of respondents, as the research was conducted only at one branch office of PT TASPEN (Persero). Therefore, the findings may not fully represent the overall conditions of all employees within PT TASPEN (Persero). Contributions: This study contributes to the field of human resource management by providing empirical evidence regarding the influence of organizational culture and organizational commitment on employee loyalty. Additionally, the findings may serve as a reference for organizations in developing more effective human resource management strategies.